Power control circuits manual - Marston, R. M. (Newnes circuits manual series., 1990)
Power Control Circuits Manual presents a comprehensive review of electronic power control. The book is comprised of eight chapters that deal with a specific aspect of power control. The text first discusses the basic principles of electrical-electronic power control, and then proceeds to presenting practical control circuits using conventional switches and relays. Chapter 3 discusses ways of using CMOS devices as low-power electronic switches, while Chapters 4 and 5 deal with AC and DC power control systems. Next, the book presents ways of controlling DC motors, and the remaining two chapt.